Community engagement and human perception in crocodile conservation: preliminary steps in Sian Ka’an Biosphere Reserve - Benítez-Moreno, Javier Arturo; Cedeño-Vázquez, José Rogelio; Castelblanco-Martínez, Delma Nataly (Frontiers in Conservation Science, 2024)
Wildlife tourism is important for the conservation of protected areas, endangered species, and to empower of local communities. Nevertheless, when guidelines and practices are not clear and correctly executed, tourism has a negative impact. We carried out semi-open interviews (n = 34) and several workshops (n = 50) with locals and tour guides in the village of Punta Allen in Sian Ka'an Biosphere Reserve, Mexico. Most respondents (69%) dedicated 2-10 min to crocodile observation, one quarter (25%) spent 11-20 min, and the remaining (6%) 21-30 min. The majority (97%) of respondents mentioned that when they see a crocodile, they approach at a 5-10 m distance and wait for the occupants of the boat to take pictures, and then leave; only one respondent (3%) said that they feed crocodiles to attract them to the boat. Most respondents (89%) said that crocodile observation does not need be improved, and it is fine the way it is currently carried out; the remaining 11% said that it could be improved. Workshops were received positively and allowed us to share information on crocodile species, their conservation and good tourism practices. It is necessary to enlighten tourism service providers about the biology and importance of crocodilian species, to promote conservation and provide services with an educational impact/focus for visitors to the reserve. There is a need to develop a communication program that provides accurate information for new service providers and renews and reinforces concepts for established providers. Additionally, we need to continuously monitor and evaluate wildlife observation activities to enhance current practices, and to determine if they are having a negative impact on crocodile behavior and biology.